Evaluation on the financial performance of the companies in Malaysia with Zmijewski model - Lam, Weng Siew; Lam, Weng Hoe; Lai, Jing Xin, Agnes; Bahaludin, Hafizah; Abdullah, Mimi Hafizah (2019)
Due to the rising competitiveness between businesses, it gets harder to earn huge profits in a business. There has been an increased emphasis on bankruptcy issue as the number of bankruptcy cases has grown over the last few decades. This has led to the evolution of numerous bankruptcy prediction models that seek to address this issue. Since there is no overnight solution to a company‟s poor financial health, a bankruptcy prediction model helps in providing the decision makers with insights into the company‟s financial status, allowing them to take early recovery actions. This study aims to predict bankruptcy of the financial firms in Malaysia. Empirical analysis using Zmijewski model was conducted. Zmijewski model measures the performance, leverage, and liquidity of a company based on three financial ratios. The data of 31 financial companies that listed on Bursa Malaysia Stock Exchange were analysed from year 2013 to 2017. The results obtained revealed that APEX, BURSA, ECM, ELKDESA, INSAS, LPI, MAA, MPHBCAP, P&O, RCECAP, TA, and TUNEPRO are the 12 financially secured companies. The significance of this study reflects the bankruptcy predictive ability of Zmijewski model whereby the bankrupt and non-bankrupt firms are identified.